Information and communication technology in A-level physics teaching and learning at secondary schools in Manicaland Zimbabwe: multiple case studies - Mlambo, Watson (Rhodes University, Faculty of Education, Department of Education, 2008)
As personal computers (PCs) and related ICTs become more and more omnipresent than ever before in institutions of education, teachers are faced with the challenge of having to teach in ICT rich environments. Some syllabuses increase this pressure by stipulating where ICT may be applied. While past research efforts have focused on presence of and/or effectiveness of ICTs on achieving various didactic goals, there is limited literature on the extent to which actual practice occurred naturally. It was the aim of this study to determine the extent to which Physics teachers and students used ICT in their usual teaching/learning ambience, referred to as natural settings in this study. Using activity theory as a theoretical lens, multiple case studies were chosen as a strategy using 10 schools, 15 Physics teachers, 20 A-level Physics students and 10 ICT teachers (computer specialists). Questionnaires, observations and informal and focus group interviews were used to elicit responses from students, teachers and computer specialists. It emerged from the case studies that despite the presence of apt ICT infrastructure in the schools and although the teachers had a positive attitude towards the use of ICT for teaching and learning of Physics, teachers were apathetic when it came to the actual use. Some of the reasons militating against use were lack of an ICT policy, school authority, and monopoly of computers enjoyed by computer studies teachers. However among students there were 'early starters' who used ICTs outside of school, a situation that tended to change the Physics learning environment. These findings led to a proposal for a post of Computer Specialist (CS) in the schools. The need for developing ICT policy at all levels namely national, Ministry of Education and the school was also proposed. Lastly staff development in the use ICT for Physics teachers was proposed as indispensable.
Keywords: Information technology -- Zimbabwe; Educational technology -- Zimbabwe; Education, Secondary -- Zimbabwe; Information technology -- Study and teaching (Secondary) -- Zimbabwe; Physics -- Study and teaching (Secondary) -- Zimbabwe; Computer-assisted instruction -- Zimbabwe